PERILAKU ETIKA DALAM PROFESI AKUNTANSI - Nggongi, Vera Rambu; Channelia, Patricia; Sandari, Tries Ellia (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2024)
This study examines ethical behavior in the accounting profession, which is a critical element in maintaining the integrity and credibility of the profession. The primary objective of this research is to analyze the factors influencing ethical decision-making by accountants, including professional pressure, compliance with standards, and social responsibility. Data were collected through a survey of accounting practitioners and analyzed using quantitative methods to identify the relationship between individual, organizational, and environmental factors with ethical behavior. The findings reveal that ethics training, organizational culture, and effective supervision significantly influence adherence to ethical principles. The implications of this study are expected to provide insights for developing ethical policies within the accounting profession.